RELASI ANTAR AKTOR DALAM KOMPETISI LAYANG-LAYANG DI DENPASAR JELANG PEMILU LEGISLATIF TAHUN 2014 - wigraheni, Wina wigraheni; Erviantono, Tedi; S.Fil.,MA, Bandiyah (Jurnal Nawala Politika, 2015)
ABSTRACT In general, the race kite competed in a simple, unlike the case with Denpasar Bali kite into an arts and culture into public appeal. See enthusiastic people who are very high and increasing number of participants race each year, it indicates that the race kite got a great welcome from the public. The existence of race kite began ogled by the actors, especially the legislative candidates who run for the legislative elections in 2014. The objective is to get the support of the voice of sekaa kites. The purpose of this study was to determine how the actors in relation to compete in a race kite in Denpasar ahead of legislative elections in 2014. In order to obtain an answer from the formulation of the problem is done with descriptive qualitative methods, such as by interviews with key informants, observations in the field, and documentation. Results from this study can be concluded is first, ahead of the legislative elections many candidates became involved in providing assistance, in the form of materials such as funding for the cost of making kites is done in their own hamlets or villages. The provision of such assistance lead to a reciprocal relationship between candidates with sekaa kites, and equally mutual benefit. Secondly, before the 2014 legislative elections individual candidates sekaa more aggressively approached them with participating enliven kite kite race in row to get closer to their constituents and keep the noise down so as not to split. Sekaa organization and kites into the vehicle and the political machine in gaining a voice in the legislative elections of 2014, this phenomenon was common in those days before the election, but it is interesting because it dihimpuni by sekaa organizations that do not necessarily exist elsewhere. Keywords: Pelangi Bali, Kites Team, Candidates, Legislative Elections